2018
DOI: 10.3390/ijms19092710
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Immunoglobulin-Like Receptors A2 and A6 are Expressed in Avian Macrophages and Modulate Cytokine Production by Activating Multiple Signaling Pathways

Abstract: The activating leukocyte immunoglobulin-like receptors (LILRAs) play an important role in innate immunity. However, most of the LILRA members have not been characterized in avian species including chickens. The present study is the first attempt at cloning, structural analysis and functional characterization of two LILRAs (LILRA2 and LILRA6) in chickens. Multiple sequence alignments and construction of a phylogenetic tree of chicken LILRA2 and LILRA6 with mammalian proteins revealed high conservation between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…27,28 LILRs also serve immunomodulatory roles in bacterial infection. [16][17][18][19][29][30][31][32][33] Unknown is the function of LILRA5 in bacterial infection. We found that LILRA5 deletion negatively regulates the immune responses in P. aeruginosa keratitis by promoting the expression of proinflammatory cytokines and TLR4 in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 LILRs also serve immunomodulatory roles in bacterial infection. [16][17][18][19][29][30][31][32][33] Unknown is the function of LILRA5 in bacterial infection. We found that LILRA5 deletion negatively regulates the immune responses in P. aeruginosa keratitis by promoting the expression of proinflammatory cytokines and TLR4 in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of miRNA-181a-5p is downregulated in the monocytes of obese subjects and cardiovascular disease patients [ 30 ]. SHP2 plays a vital role in regulating macrophage proliferation via a direct activation of the MAPK pathway [ 31 ]. A previous study has shown that the inactivation of SHP2 can augment IL-4-mediated enhancement of M2 polarization in vitro [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of lncRNAs is involved in the pathogenesis of various diseases [24]. Recent studies have suggested that lncRNAs potentially impact the expression levels of miRNA targets by competing for miRNAs [25]. Evidences have shown that MEG8 contributed to epigenetic progression of EMT of lung and pancreatic cancer cells, and suppressed the proliferation and migration of both the vascular smooth muscle cell (VSMC) and trophoblast cells [26,27].…”
Section: Discussionmentioning
confidence: 99%